Long-Term Impact of Parental Post-Traumatic Stress Disorder Symptoms on Mental Health of Their Offspring After the Great East Japan Earthquake - Honda, Yukiko; Fujiwara, Takeo; Yagi, Junko; Homma, Hiroaki; Mashiko, Hirobumi; Nagao, Keizo; Okuyama, Makiko; Ono-Kihara, Masako; Kihara, Masahiro (Frontiers in Psychiatry, 2019)
Longitudinal studies of the long-term psychological impact of the Great East Japan Earthquake (GEJE) on parents and their children have been limited. The current study aimed to monitor parents’ post-traumatic stress disorder (PTSD) symptoms and behavioral problems among their children over time and to analyze their long-term associations among the survivors of the GEJE. We used data from the GEJE Follow-up for Children study, which recruited 4- to 6-year-old children and those children’s parents immediately after the GEJE in March 2011, with ongoing follow-up. Children’s total, internalizing, and externalizing behavioral problems were assessed using the Child Behavior Checklist (CBCL), and parental probable PTSD was assessed using the Impact of Event Scale-R (IES-R), in 2012 (baseline) and 2014 (follow-up). Parental PTSD symptoms and children’s behavioral problems declined slightly over time, and both showed a significant correlation between the surveys (r = 0.55–0.77, P < 0.001). The association between parental PTSD symptoms and children’s behavioral problems was investigated using multivariate logistic regression analysis adjusting for baseline children’s behavioral problems and other potential confounders. Cross-sectionally, while no significant association was detected in 2012, all types of children’s behavioral problems exhibited significant positive associations with parental PTSD symptoms in multiple logistic regression analysis adjusted odds ratio (AOR) = 3.03, 3.30, and 5.34 for total, internalizing, and externalizing behavior problems, respectively. Maternal educational attainment level (higher than high school education) showed a significant negative association with children’s total and externalizing behavioral problems (AOR = 0.30 and 0.13, respectively) in 2014. Longitudinally, parental PTSD symptoms in 2012 showed a significant association with children’s internalizing behavioral problems in 2014 after adjusting for children’s behavioral problems in 2012 and parental PTSD symptoms in 2014 (AOR = 4.62). These results suggest that the effect of the GEJE on parental PTSD symptoms and children’s behavioral problems was long-term, lasting for at least 3 years. These possibilities should be carefully considered in mental health support for parents and their offspring in areas affected by the GEJE.